Breaking up prolonged sitting with moderate-intensity walking improves attention and executive function in Qatari females - Bryna C. R. Chrismas (6820142) (2019)
Background Cultural, environmental and logistical factors promote a sedentary lifestyle within Qatar, particularly for females. Sedentary behaviour is acutely associated with poor cognitive function and fatigue, and chronically may be implicated with cognitive decline (i.e. Alzheimer’s disease). Purpose To examine the effects of breaking up sitting with short-duration frequent walking bouts on cognitive function and fatigue in Qatari females. Method Eleven sedentary (sitting ≥7 h/day) females completed three visits; the first being familiarisation. In a cross-over randomised manner, experimental visits two and three were identical, except participants either remained seated for 5-h (SIT) or interrupted their sitting every 30-min with a 3-min moderate-intensity walk (WALK) on a motorised treadmill. The Computerised Mental Performance Assessment System (COMPASS) assessed cognition at baseline (-15-min), and then at 2.5-h and 5-h into the experimental conditions. Specific COMPASS tasks employed were; serial-3 subtractions (2-min), serial-7 subtractions (2-min), simple reaction time (RT; 50 stimuli), rapid visual information processing [RVIP (5-min)], choice reaction time (CRT; 50 stimuli), and Stroop (60 stimuli); and a visual analogue scale for fatigue (VAS-F) was completed at the same time intervals. Results There was a significant condition effect for CRT (f = 26.7, p = 0.007). On average CRT was 101 s (95% CI = -47 to -156 s) quicker in WALK compared to SIT. There was a significant time effect for CRT (f = 15.5, p = 0.01). On average CRT was 134 s slower at 5-h compared to baseline (p = 0.006; 95% CI = -64 to -203 s), and 114 s slower at 5-h compared to 2.5-h (p = 0.01; 95% CI = -44 to -183 s). There was a significant interaction effect for RT in the Stroop incongruent task (f = 10.0, p = 0.03). On average RT was 210 s quicker at 2.5-h in WALK compared to SIT (p = 0.01; 95% CI = -76 to -346 s). Conclusion Breaking up prolonged sitting with moderate-intensity walking offers an ecologically valid intervention to enhance some aspects of cognitive function, whilst not affecting fatigue in sedentary Qatari females. Whilst these findings are promising, the long-term effects of breaking up sitting on cognitive function requires testing before population level recommendations can be made. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0219565